PENGARUH PERUBAHAN PERATURAN PAJAK PERTAMBAHAN NILAI (PPN) DAN SOSIALISASI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK (STUDI: AEON MALL BSD) - Ruenli, Evangeline Davina; Trisnawati, Estralita (UNIKA Santo Thomas, 2025)
Taxes are mandatory contributions paid by citizens to the government that are used to finance various public needs and state development. A good tax system can create economic stability, reduce social inequality, and support infrastructure development and public services. Tax is an important instrument in state financing and development. The main purpose of this research is to examine the effect of understanding changes in VAT regulations and tax socialization on taxpayer compliance. This study uses primary data in the form of numbers and will be analyzed using statistics with the aim of testing the hypothesis. The population of this study were 106 non-food and beverages tenants at AEON Mall BSD City. The cluster sampling method was used by distributing questionnaires offline to AEON Mall BSD City which were then analyzed using SPSS 29.0 for windows. The distribution process was carried out offline using questionnaire paper on September 28, 2024. The results of this study indicate that understanding changes in VAT regulations and tax socialization have a positive significant influence on taxpayer compliance